1993
DOI: 10.1007/bf02513596
|View full text |Cite
|
Sign up to set email alerts
|

Host plant conspicuousness and the distribution of eggs and larvae in the butterfly, Anthocharis scolymus (Lepidoptera: Pieridae)

Abstract: SummaryWe investigated how the distribution pattern of eggs and larval on the host plant, Turritus glabra, was influenced by the oviposition behavior of the pierid butterfly Anthocharis scolymus. Females searched for the host plants visually and they frequently approached taller host plants with sparse surrounding vegetation. After encountering host plants, oviposition behavior of females was independent of host plant characteristics such as height, density, and type of surrounding vegetation. A female laid eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Because of egg cannibalism, ospring laid on plants bearing conspeci®c eggs or larvae were less likely to survive than those on plants without. This consequence is consistent with previous reports in Anthocharis, stating that a high density of eggs and larvae causes severe intraspeci®c competition for resources and leads to cannibalism resulting in a reduction of survival, while the egg ®rst laid is the most likely to survive in that it can escape cannibalism when several eggs are laid on a single plant (Courtney 1981;Courtney and Duggan 1983;Masumoto et al 1993;Dempster 1997). The data came from only one year (1993).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Because of egg cannibalism, ospring laid on plants bearing conspeci®c eggs or larvae were less likely to survive than those on plants without. This consequence is consistent with previous reports in Anthocharis, stating that a high density of eggs and larvae causes severe intraspeci®c competition for resources and leads to cannibalism resulting in a reduction of survival, while the egg ®rst laid is the most likely to survive in that it can escape cannibalism when several eggs are laid on a single plant (Courtney 1981;Courtney and Duggan 1983;Masumoto et al 1993;Dempster 1997). The data came from only one year (1993).…”
Section: Discussionsupporting
confidence: 90%
“…The objective of this study is to evaluate how female eclosion and oviposition timing aects ospring survival of the pierid butter¯y, Anthocharis scolymus (L.) that feeds on crucifers. Some previous studies have shown that oviposition preferences in A. scolymus are important for ospring survival and growth (Masumoto et al 1993;A. Kurachi, unpublished work).…”
Section: Introductionmentioning
confidence: 94%
“…The effects of host plant density on movement patterns of adult butterflies have been well documented (Cromartie 1975;Kobayashi 1966;Jones 1977;Rausher 1983;Masumoto et al 1993). Female adults of Anthocharis scolymus search for their host plants by sight, and eggs are aggregated on the conspicuous host plants (Masumoto et al 1993). Female adults of P. rapae also search for their host by sight but do not utilize plants in shaded environments (Osaki 1980).…”
Section: Effect Of Nonhost and Host Plant Density On Fruit Productionmentioning
confidence: 99%
“…When multiple larvae are reared on a single tray, there is a decrease in the amount of food available for each larva leading to competition for resources resulting in retarded growth (Masumoto et al, 1993). Study of the mode of distribution of the food has led to the conclusion that the silkworm Bombyx mori feeds continuously, making a series of small feedings, and although the ingested quantities vary a great deal during a 24-hour period, excretion goes on regularly (Legas, 1958).…”
Section: Introductionmentioning
confidence: 99%